Dynamical aspects of nuclear fission : proceedings of the 6th International Conference, Smolenice Castle, Slovak Republic : 2-6 October 2006 - Kliman, Jan; Itkis, M. G.; Gmuca, S̆. (Stefan) (World Scientific, 2008)
This proceedings volume is sixth in the series of international conferences covering the fission, quasi-fission, fusion-fission phenomena and synthesis of superheavy nuclei, mainly at low or near barrier energies. Both experimental and theoretical issues are covered. The topics are discussed by a group of participants, and an overview of the current activities in the field is given.